Evaluating the adsorption performance of functional building material with HCHO remover - Jung, Chuloh; Alqassimi, Nahla; El Samanoudy, Gamal (Frontiers in Built Environment, 2022)
Dubai Municipality is making significant efforts to reduce the concentration of chemical substances in major buildings via Green Building Regulations & Specifications. However, it has limitations to the problem because it simply regulates the indoor air concentration of some harmful substances from building materials. The functional building materials capable of adsorbing and decomposing indoor pollutants such as Formaldehyde (HCHO) and Volatile Organic Compounds (VOCs) are gradually spreading. This paper aims to evaluate the performance of functional building materials and analyze the effect of improving the indoor air environment. As a methodology, the investigation was done to research trends and standards for functional building standards. 20 liters small chamber experiment was performed for wallpaper with 0 %, 5 %, 7 %, 10 %, and 15 % of the ethylene urea (C5H10N2O3), HCHO remover. The result showed standard wallpaper’s adsorption rate on the 7th day was 6.21 %. The formaldehyde remover adsorption rate for 7 days was 50.43 % when formaldehyde remover was added at a 5wt % (weight percentage); 60.21 % when it was added at 7wt %; 63.45 % when it was added at 10wt %; and 73.58 % when it was added at 15wt %. The adsorption rate on the 7th day with 7wt %, 10wt %, and 15wt % HCHO remover showed a 60 % or more (ISO 16000-24 standard). However, wallpaper with 15wt %, displayed the highest value, was 5.736 μg/m2, which did not satisfy the ISO 16000-24 standard (6.000 μg/m2). It was statistically proven when the amount of the HCHO remover is increased; the adsorption performance is improved in proportion to the amount added. This study will serve as primary data to prepare UAE standards for the functional building materials with adsorption and decomposition performance of harmful chemicals, moisture absorption and moisture-proof performance, and antibacterial/anti-fungal performance.